Psilocybin for Treating Psychiatric Disorders: A Psychonaut Legend or a Promising Therapeutic Perspective? - Maurizio Coppola; Francesco Bevione; Raffaella Mondola (MDPI AG, 2022)
Psychedelics extracted from plants have been used in religious, spiritual, and mystic practices for millennia. In 1957, Dr. Hofmann identified and synthesized the prodrug psilocybin, a substance present in more than 200 species of psychedelic mushrooms. Although there were limitations related to the scientific design of many studies, clinical observations performed during the 1950s and 1960s showed a potential therapeutic effect of psilocybin for patients affected by depressive symptoms, anxiety, and conversion disorder. Psilocybin was classed as a schedule I substance in 1970, but the fascination with psychedelics has remained almost unchanged over time, promoting a new scientific interest starting in the 1990s. Recent studies have provided further evidence supporting the suggestive hypothesis of the therapeutic use of psilocybin for treating various psychiatric disorders, including pathological anxiety, mood depressive disorder, and addiction.